Developing entrepreneurial ecosystems in academia - Tunio, Muhammad Nawaz; Shaikh, Erum; Chaudhary, Kiran; Tiep, Le Thanh (IGI Global, 2022)
"This book discusses academic entrepreneurship that focuses on the educated population who are learning and working in the universities and how they can create an entrepreneurial ecosystem so that academics can establish the role of entrepreneurship after teaching and research
Includes bibliographical references and index
Chapter 1. The role of the university in entrepreneurial ecosystems: how to better integrate entrepreneurial education into a university curriculum -- Chapter 2. Learning creativity and students' performance: the academia contributions -- Chapter 3. A study of the convergence between entrepreneurship, government policy, and higher education in Oman: entrepreneurial ecosystem perspective -- Chapter 4. The role of heis in creating social academic entrepreneurial ecosystems: a case of a liberal arts University in Pakistan -- Chapter 5. Entrepreneurial success and opportunities for women and female youth in Pakistan: case study in Pakistani Women University -- Chapter 6. Critical assessment of socio-intercultural entrepreneurship: a case on a postgraduate program in economics and international business -- Chapter 7. Socio-intercultural entrepreneurship capability building and development -- Chapter 8. Carving new dimensions for entrepreneurial management: a qualitative inquiry from an Asian subcontinent region -- Chapter 9. Career predilections and options to opt occupation for the youth in Pakistan -- Chapter 10. Economic development and growth perspectives in entrepreneurship -- Chapter 11. Impact of restructuring on employee productivity amidst COVID-19 in Pakistan: a case study of SMEs -- Chapter 12. The impact of university curricula on financial education of millennials -- Chapter 13. Sociopreneurship: program of literation technology and academic assistance to MSMEs in increasing the sales market in industry era 5.0. - Mode of access: World Wide Web
Keywords: Entrepreneurship -- Study and teaching (Higher) -- Developing countries; Entrepreneurship -- Study and teaching (Higher); Developing countries; Aufsatzsammlung